Electrical properties of Sb and Cr-doped PbZrO3-PbTiO3-PbMg1/3Nb2/3O3 ceramics - Whatmore, Roger W.; Molter, O.; Shaw, Christopher P. (Elsevier, 2003)
The pyroelectric, dielectric and DC resistive properties of Sb and Cr-doped ceramics with a base composition of Pb(Mg1/3Nb2/3)0.025(Zr0.825Ti0.175)0.975O3 have been studied. Sb doping has been shown to produce a linear reduction in Curie temperature (TC=−22z+294 °C) with concentration (z) and to give an increase in pyroelectric coefficient from 250 to 310 μCm−2 K−1 for z increasing from 0 to 3 at.%. It also produces first a reduction and then an increase in both dielectric constant and loss, so that the 33 Hz pyroelectric figures of merit (FOM's) are as follows: FV peaks at 3.8×10−2 m2 C−1 and FD peaks at 1.2×10−5 Pa−1/2. The resistivity is increased substantially from 1.1×1011 to ca 6×1011 Ωm with 1 at.% Sb, thereafter changing little. The behaviour has been explained in terms of Sb acting as a donor ion, reducing oxygen vacancy concentrations up to 1 at.%, with conductivity dominated by hole hopping between traps (Ea=0.59±0.05 eV) that are not changed by the Sb doping. It is concluded that additions of higher levels of Sb do not produce electron-mediated hopping conduction. The Cr additions have no effect upon TC, but reduce dielectric constant and loss, pyroelectric coefficient and resistivity at doping levels up to 3 at.%. The FOM FV peaks at 3.6×10−2 m2 C−1 and FD at 1.9×10−5 Pa−1/2. The behaviour of the electrical resistivity as a function of dopant level is shown to produce a linear ln(σo) vs z−1/3 dependence (σo=DC conductivity), as would be expected for hole hopping conduction between Cr3+ sites, with an Ea=0.38±0.03 eV.
Keywords: Pb(Mg,Nb,Zr,Ti)O3; Perovskites; PZT